Heteropolymerization of α-1-antitrypsin mutants in cell models mimicking heterozygosity - Laffranchi, Mattia; Berardelli, Romina; Ronzoni, Riccardo; Lomas, David A; Fra, Annamaria (Human molecular genetics, 2018)
Abstract The most common genotype associated with severe α-1-antitrypsin deficiency (AATD) is the Z homozygote. The Z variant (Glu342Lys) of α-1-antitrypsin (AAT) undergoes a conformational change and is retained within the endoplasmic reticulum (ER) of hepatocytes leading to the formation of ordered polymeric chains and inclusion bodies. Accumulation of mutated protein predisposes to cirrhosis whilst plasma AAT deficiency leads to emphysema. Increased risk of liver and lung disease has also been reported in heterozygous subjects who carry Z in association with the milder S allele (Glu264Val) or even with wild-type M. However, it is unknown whether Z AAT can co-polymerize with other AAT variants in vivo. We co-expressed two AAT variants, each modified by a different tag, in cell models that replicate AAT deficiency. We used pull-down assays to investigate interactions between co-expressed variants and showed that Z AAT forms heteropolymers with S and with the rare Mmalton (Phe52del) and Mwurzburg (Pro369Ser) mutants, and to a lesser extent with the wild-type protein. Heteropolymers were recognized by the 2C1 mAb that binds to Z polymers in vivo. There was increased intracellular accumulation of AAT variants when co-expressed with Z AAT, suggesting a dominant negative effect of the Z allele. The molecular interactions between S and Z AAT were confirmed by confocal microscopy showing their colocalization within dilated ER cisternae and by positivity in Proximity Ligation Assays. These results provide the first evidence of intracellular co-polymerization of AAT mutants and contribute to understanding the risk of liver disease in SZ and MZ heterozygotes.